Functional redundancy in the toxic pathway of Bt protein Cry1Ab, but not Cry1Fa, against the Asian corn borer - Xingliang Wang; Yujin Yue; Yuqian Zhai; Falong Wang; Xuna Zhuang; Shuwen Wu; Yihua Yang; Bruce E. Tabashnik; Yidong Wu (Proceedings of the National Academy of Sciences, 2025)
Crops genetically engineered to produce insecticidal proteins from the bacterium Bacillus thuringiensis (Bt) have been used extensively to control some major crop pests, but their benefits decrease when pests evolve resistance. Better understanding of the genetic basis of resistance is needed to effectively monitor, manage, and counter pest resistance to Bt crops. Resistance to Bt proteins in at least 11 species of Lepidoptera, including many important crop pests, is associated with naturally occurring mutations that disrupt one or more of three larval midgut proteins: cadherin and ATP-binding cassette proteins ABCC2 and ABCC3. Here, we determined how CRISPR/Cas9-mediated mutations disrupting cadherin, ABCC2, and ABCC3 singly and in pairs affect resistance to Bt proteins Cry1Ab and Cry1Fa in the Asian corn borer ( Ostrinia furnacalis ), which is the most damaging pest of corn in Asia and is closely related to the European corn borer ( Ostrinia nubilalis ), a major pest in Europe and North America. The results from bioassays of six knockout strains and their parent susceptible strain support a model in which Cry1Ab can kill larvae via one path requiring ABCC2 or another path requiring cadherin and ABCC3, whereas Cry1Fa uses only the first path. The model’s predictions are generally supported by results from genetic linkage analyses and responses to Cry1Ab and Cry1Fa of Sf9 cells and Xenopus oocytes modified to produce cadherin, ABCC2, and ABCC3 singly or in pairs. The functional redundancy identified here for Cry1Ab could sustain its efficacy against O. furnacalis and may exemplify a widespread natural strategy for delaying resistance.